REKONSTRUKSI PENDIDIKAN KEWARGANEGARAAN BERBASIS NILAI PANCASILA DALAM MENGHADAPI ERA SOCIETY 5.0 - Astia Aprianti; Ahmad Arifi (Dar el-Ilmi : Jurnal Studi Keagamaan, Pendidikan dan Humaniora, 2026)
The transformation of Civic Education in response to the dynamics of Society 5.0 requires integrating digital competencies and humanistic values grounded in Pancasila. This study aims to analyze the direction of pedagogical transformation in Civic Education and to identify ways to integrate Pancasila values into adaptive, context-based learning in digital environments. The research employs a qualitative descriptive approach using a narrative literature review of 32 reputable scholarly articles published between 2019 and 2025, focusing on themes such as Civic Education, Pancasila values, digital citizenship, and pedagogical innovation. The findings indicate a prevailing dominance of theoretical approaches in instruction, limited integration of digital civic competencies, and a gap between curriculum design and classroom implementation. Furthermore, participatory, experiential, and contextual learning models demonstrate significant potential to strengthen the internalization of Pancasila values and enhance students’ digital civic awareness. This study contributes to the reinforcement of a constructivist paradigm in Civic Education, positioning values as outcomes of experiential learning rather than mere knowledge transmission. Therefore, Civic Education needs to be reoriented toward an integrative and adaptive approach that supports the development of civic character aligned with the demands of Society 5.0.